Competition reforms and collaborative federalism: a dynamic multiregional applied general equilibrium analysis - John Robert Madden; James Giesecke (European Regional Science Association (ERSA), 2002)
In 1995 all Australian state and territory governments entered into an agreement with the federal government to introduce a comprehensive program of national competition policy (NCP) reforms. A number of studies have attempted to assess the benefits of these reforms by (i) estimating, via data envelopment analysis or similar techniques, the productivity gap between Australian industries affected by the reforms and their foreign counterparts, and (ii) then modelling the long-run effects of bringing the relevant Australian industries to world-best-practice levels of efficiency. These studies have been criticised for having severely overestimated the efficiency gains from NCP, and for ignoring the associated labour market adjustments. In this paper we take advantage of FEDERAL-F's historical modelling and forecasting capabilities to take a new approach to the problem. First, to measure the efficiency gains from NCP, we use the observed changes in efficiency in one of the sectors subject to NCP reforms (utilities) immediately after the introduction of NCP (rather than following the earlier approach of making a comparison between actual and best-practice levels of productivity). The changes in the utilities sector's primary factor productivity pre- and post- the introduction of NCP are calculated during historical simulations with FEDERAL-F. We investigate the impacts that the changes in observed productivity improvements have had on regional indicators of aggregate economic activity, with particular attention to indices of regional labour market adjustment costs. The changes in these indices provide measures of the value of labour inputs that are lost as implementation of the NCP alters the flow of people between different labour market categories.
Keywords: 330